Reshaping Governance and Building Ethical Resilience in Islamic Economic Order: Legal Reform, Institutional Practice, and Societal Relevance - Hidayah, Nur (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2025)
This issue of Al-Iqtishad emerges amid pressing demands to realign Islamic economic governance with its ethical foundations and public purpose. As both global and domestic economies navigate financial volatility, digital disruption, and socio-ecological urgencies, this volume advances a critical and multidisciplinary reflection on how Islamic economics can remain normatively authentic while addressing institutional gaps, governance inconsistencies, and societal inequities. The first two papers delve into Indonesia’s recent structural transformation in Islamic banking through the spin-off policy. Mahfudz et al. go beyond legal compliance to diagnose deeper jurisprudential tensions in existing contracts during the spin-off mandate. Their proposed framework—rooted in qawāʿid fiqhiyya and maqāṣid al-sharī‘a—is not merely a technical legal tool but a powerful proposition to anchor contract governance in moral reasoning. In parallel, Megawati et al.’s case study of Bank Riau Kepri’s conversion reveals the tensions between regulatory mandates and institutional capacity, underlining the need for reform that is as culturally sensitive as it is structurally sound. In a powerful departure from orthodox economic discourse, Al Munawar and Syaputra problematize the IDRT (Indonesian Rupiah Token) stablecoin phenomenon as both a legal and theological dilemma. Their analysis raises a provocative question: Can Islamic finance remain ethically distinct if it mimics the speculative and sovereign-challenging architecture of crypto-finance? The absence of a cohesive Sharia response to digital currency reveals a theological vacuum at the heart of Islamic economic modernity. Equally compelling is the ethnographic intervention by Nuraini and Solichin, who examine the Javanese Sinoman tradition to question mainstream Islamic finance’s obsession with formal contracts and time value. By foregrounding reciprocity, trust, and community recognition, they argue that justice in Islamic economics must be culturally embedded and not solely derived from textual legalism. Their study invites us to decolonize Islamic economic ethics and reinvigorate it with lived local wisdom. On the frontier of financial literacy and economic justice, Shalihah et al. offer more than a model of community financial education—they expose the fragility of coastal communities caught between financial exclusion and exploitative investments. Their work reframes Islamic literacy as an emancipatory praxis—a call to build financial vigilance from below rather than relying solely on top-down regulation. In the realm of capital markets, Agara and Hariyani call for a normative realignment of Sukuk with global sustainability goals. Yet unlike previous green Sukuk studies, they situate the discourse in legal justice, urging regulators to design instruments that not only finance renewable energy but also operationalize intergenerational equity and ecological trusteeship (amānah). Their work shifts Islamic finance from financing ethics to ethical financing. Mukhlisin revisits the halal economy through the lens of Islamic political economy, boldly arguing that technocratic halal certification has been stripped of its ideological purpose. Her critique reminds us that Islamic economic legitimacy cannot be outsourced to procedural regulation—it must be rooted in political will, institutional independence, and distributive justice. This paper is a timely intervention as Indonesia expands its halal industrial zone without critically reflecting on its governance models. Desiana et al. diagnose the regulatory myopia that continues to hinder Sukuk’s integration with Indonesia’s real economy. While previous studies highlight market limitations, this paper reveals a deeper issue: the regulatory imagination itself has not caught up with the expansive potential of Islamic financial instruments. Their empirical insights demand a rethinking of OJK’s institutional capacity in enabling a more inclusive financial architecture. Gusniarti’s study on Muslimahpreneurs in the post-pandemic era weaves legal anthropology with crisis management. She reframes resilience not as a passive coping mechanism, but as an active reassertion of faith, agency, and legal literacy among Muslim women entrepreneurs. Her findings remind us that Islamic economics must account for gendered realities and not romanticize resilience without addressing structural precarity. The closing paper by Kusumawardani et al. proposes an integrated Six Capitals approach to Waqf asset management, using Muhammadiyah as a reference point. This is not merely a technical innovation—it represents a philosophical return to the foundational logic of Waqf: stewardship, transparency, and social transformation. Their study suggests that to realize Waqf’s full potential, Islamic philanthropy must embrace multi-dimensional accountability frameworks that bridge spiritual intention with measurable impact. Together, these ten papers challenge us to reimagine Islamic economics beyond compliance and toward conscience. They call for an epistemic shift from normative formality to ethical substance, from fragmented implementation to systemic coherence. As editor, I am proud to present this volume as a milestone in our collective effort to make Islamic economics not just as a normative ideal, but as a transformative force shaping equitable and sustainable futures.